Electronic Structure Modulation Induced by Cobalt‐doping and Lattice‐Contracting on Armor‐Like Ruthenium Oxide Drives pH‐Universal Oxygen Evolution. Issue 4 (24th November 2022) - Gong, Rui; Liu, Bowen; Wang, Xiaolei; Du, Shichao; Xie, Ying; Jia, Wanqi; Bian, Xinxin; Chen, Zhimin; Ren, Zhiyu
Abstract: Exquisite design of RuO2 ‐based catalysts to simultaneously improve activity and stability under harsh conditions and reduce the Ru dosage is crucial for advancing energy conversion involving oxygen evolution reaction (OER). Herein, a distinctive cobalt‐doped RuOx framework is constructed on Co3 O4 nanocones (Co3 O4 @CoRuOx ) as a promising strategy to realize above urgent desires. Extensive experimental characterization and theoretical analysis demonstrate that cobalt doped in RuOx lattice brings the oxygen vacancies and lattice contraction, which jointly redistribute the electron configuration of RuOx . The optimized d ‐band center balances the adsorption energies of oxygenated intermediates, lowing the thermodynamical barrier of the rate‐determining step; and meanwhile, the over‐oxidation and dissolution of Ru species are restrained because of the p ‐band down‐shifting of the lattice oxygen. Co3 O4 @CoRuOx with 3.7 wt.% Ru delivers the extremely low OER overpotentials at 10 mA cm −2 in alkaline (167 mV), neutral (229 mV), and acidic electrolytes (161 mV), and super operating stability over dozens of hours. The unprecedented activity ranks first in all pH‐universal OER catalysts reported so far. These findings provide a route to produce robust low‐loading Ru catalysts and an engineering approach for regulating the central active metal through synergy of co‐existing defects to improve the catalytic performance and stability. Abstract : Cobalt‐doped RuOx armor‐like shells are rationally grafted on Co3 O4 nanocones to construct the robust catalysts with the small Ru usage, which is capable of energetically and steadily catalyzing OER in pH‐universal media, profiting from the synergistic effect of charge redistribution caused by the cobalt doping and the associated defect, and porous structure effect to expose rich active sites.